A Novel Thermal Module with 3-D Configuration Pulsating Heat Pipe for High-Flux Applications - Chih-Yung Tseng; Ho-Meng Wu; Shwin-Chung Wong; Kai-Shing Yang; Chi-Chuan Wang (Energies, 2018)
A pulsating heat pipe (PHP) contains a wickless design with aligned serpentine tube configuration whose simple structure offers a comparatively easy manufacturing capability. The bends with large curvature are often used for serpentine PHPs. This eventually results in a decline in effective contact surface area between evaporator/condenser and PHP circuitry, thereby impairing the benefit of the wickless design of a PHP. A novel thermal module featuring a 3-D configuration pulsating heat pipe, an evaporator, and a fin-and-tube condenser is proposed to tackle the high-flux application. Methanol is used as the working fluid with a filling ratio of around 60%. Test results indicate the thermal resistance of the proposed module varies from 0.148 K/W to 0.0595 K/W when the supplied power changes from 100 to 1000 W. The proposed thermal module can handle a supplied power up to 1 kW and the corresponding power or heat flux is much higher than any existing literatures.